All-Arthroscopic Foveal Triangular Fibrocartilage Complex Tendon Reconstruction - Tang, Camelia Q. Y.; Jiang, Jackson K. H.; Chin, Andrew Y. H.; Choudhury, Muntasir M. (Journal of Wrist Surgery, 2022)
Background In symptomatic chronic injury of ulnar-sided tear of the triangular fibrocartilage complex, reconstruction techniques involving foveal reconstruction with palmaris longus tendon graft using the method described by Bain have been described with good outcomes.Description of Technique With increasing popularity of wrist arthroscopy to address various wrist pathologies, we present our technique of arthroscopic foveal reconstruction. We also include a step-by-step description of the procedure with illustrations, with aims to aid surgeons in executing itConclusion Unlike other arthroscopic techniques described, this involves single osseous ulnar tunnel and performed completely arthroscopically, allowing an end result similar to Bain's open technique.
Keywords: wrist arthroscopy; triangular fibrocartilage complex; foveal reconstruction; DRUJ instability; distal radioulnar joint